Analisis Faktor Pengendalian Tingginya Kadar Air Pada Produksi Crude Palm Oil Melalui Pendekatan SPC dan FMEA Di PT Socfindo Seunagan - Nissra, Ajulia; Saputra, Arie (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
PT. Socfindo Seunagan is a company unit of PT. Socfindo Indonesia which is engaged in oil palm plantations and processing of oil palm fruit or Fresh Fruit Bunches into Crude Palm Oil. Based on observations made at PT. Socfindo Seunagan, the type of damage that most dominates the decline in CPO quality is high water content which is not in accordance with the standards set by the company, namely 0.5%. The purpose of this study was to identify the factors that cause high water content in CPO products using the FMEA method and control using the SPC method. The results of the FMEA method obtained that the highest Risk Priority Number (RPN) value for 9 factors caused the vacuum dryer machine not to operate properly at 567. Through the SPC method, it was found that the influence of these causal factors had a percentage of 29% of the other 8 factors. Based on the determination of the control chart, the center line is 243, the upper control line is 745 and the lower control line is -260. This indicates that the causative factors have a major influence on the high water content of CPO. From the fishbone diagram the vacuum dryer machine does not operate properly due to human factors, machine factors, materials and method factors.